IMPROVEMENT OF MARKETING TECHNOLOGIES IN ENTERPRISES OF THE FOOD INDUSTRY - Baymukhamedova Gulnoza Fattakhovna (Western European Studies, 2025)
Improving marketing technologies at food industry enterprises is one of the important and pressing issues. Increased competition in this area, changes in consumer demand and desire, as well as global economic trends require updating marketing strategies. Food industry enterprises need to use modern marketing technologies to successfully market their products and increase brand reputation.
Keywords: food industry; enterprises; marketing